The integration of monitoring and evaluation practices into Non-Profit Organisations: a South African perspective in the Western Cape - McGill, Lauren (My University, 2020)
Monitoring and Evaluation (M&E) of programmes offered by Non-Profit Organisations (NPOs) has become common practice in South Africa. Programme evaluation has historically formed part of an accountability and compliance requirement of donors, but shifting to a more Africa-rooted approach, it can and should equally be seen as an indispensable tool NPOs utilise to develop, interpret and iterate on their programmes. The purpose of this research study was to explore the integration of Monitoring and Evaluation practices into NPOs within the Western Cape, South Africa. For this research, a qualitative approach and a collective case study design was employed, with the purpose to explore Monitoring and Evaluation practices. Ethics clearance was received by the University of the Witwatersrand and purposive sampling was utilised to select the 12 participants. The study sample was comprised of one participant each from ten NPOs and two key informants, one representing a donor organisation and one representing a M&E specialist organisation, based in the Western Cape, South Africa. During the data collection process, three different semi-structured interview guides were used as research instruments during face-to-face interviews with the three different groups of participants. The data was analysed utilising thematic analysis. This research contributes to the knowledge generation of how NPOs in the Western Cape utilise M&E practices within their programmes. The study made a number of findings including: A high degree of collaborative M&E within organisations, with a desire to include the voices of the people for whom the development work is designed; Difficulty in differentiating between donors as there are such a variety, each of which has their own expectations and systems; Paper-based data systems appear to be the norm, with a generally poor grasp of technology amongst NPOs. Based on these findings the study has led to the development of an M&E checklist that NPOs could utilise when considering their programme planning and design
A report on a research study presented to The Department of Social Work, School of Human and Community Development, Faculty of Humanities, University of the Witwatersrand in partial fulfilment of the requirements for the degree Masters of Arts in the field of Social Development, 2020